Modern methods and preservation of collections (Confluenţe Bibliologice, 2025)
Scientiﬁc Library aims to preserve and conserve documents to meet the informational, educational, cultural user needs. Its collection numbered 1 023 155 documents. One of the management object of librarians work is the management, preservation, conservation of collections for preventing their degradation. The ﬁrst step in the care of collections is to understand and eliminate or minimize conditions that can cause damage. The paper presents methods of preservation and conservation of library collections.
Keywords: digitization of collections; conservation of collections